THE EFFECT OF NUMBERED HEADS TOGETHER STRATEGY TOWARD STUDENTS’ SPEAKING SKILL - Ulfah Dina Maryanti; Hermawati Syarif; Refnaldi Refnaldi (Proceedings of ISELT FBS Universitas Negeri Padang, 2018)
Teacher needs better strategy to help students in teaching speaking of spoken text. Numbered Heads Together is a cooperative learning strategy that holds each student accountable for learning materials in order to improve students’ speaking skill. The purpose of this research was to find out the effect of Numbered Heads Together strategy toward the students’ speaking skill of spoken text. This research was quasi-experimental research. The population of this research was the eleventh grade of senior high school located in Bengkulu province. Two classes were randomly selected as sample, namely XI IPS B as experimental class and XI IPS A as control class. The reseacher used speaking test to collect the data. The data were analyzed by using t-test. The result shows that Numbered Heads Together (NHT) strategy gives better result than Pair Work (PW) strategy on teaching speaking of spoken text.